Acute Severe Autoimmune Hepatitis: Corticosteroids or Liver Transplantation?. Issue 6 (25th April 2019) - Rahim, Mussarat N.; Liberal, Rodrigo; Miquel, Rosa; Heaton, Nigel D.; Heneghan, Michael A.
Abstract : Acute severe presentations of autoimmune hepatitis (AIH) represent a challenge for the transplant community. As a disease, it is poorly characterized, and there is a weak evidence base to guide diagnosis and treatment. Early identification of acute severe AIH is key because it determines the initiation of corticosteroids, which can be lifesaving. However, their use in this setting remains controversial. The Model for End‐Stage Liver Disease score, severity of coagulopathy, and grade of encephalopathy may be predictors of outcome with corticosteroid therapy. The optimal timing of liver transplantation (LT) can be difficult to determine and, as such, the decision to proceed to transplantation should not be delayed by protracted courses of corticosteroids. The aim of this review is to better characterize this subset of patients; to differentiate them clinically, serologically, and histologically from chronic AIH and other causes of acute liver failure; and to present the role, predictors, and optimal timings of corticosteroid therapy and LT. Although this review is specific to adults, many principles hold true for the pediatric population.